Fascial techniques for lower limb injury prevention in triathlon. A systematized literature review & workshop - Heinrich, L.; Lohmann, T. M. (Satakunta University of Applied Sciences, 2020)
Background: Triathletes compete in swimming, running and cycling. Long training hours and competitions generates train on the body and increase the risk of injuries. Especially overuse injuries are common amongst triathletes and can be traced back to fascia. As fascia techniques can improve the range of motion (ROM) of the lower extremity, incorporating those into the training regimen can have a positive impact on injury prevention.